2019
DOI: 10.1038/s41598-019-56455-2
|View full text |Cite
|
Sign up to set email alerts
|

Effective lung-targeted RNAi in mice with peptide-based delivery of nucleic acid

Abstract: We have previously developed efficient peptide-based nucleic acid delivery vectors PF14 and NF55, where we have shown that these vectors preferentially transfect lung tissue upon systemic administration with the nucleic acid. In the current work, we have explored the utilization and potential of these vectors for the lung-targeted gene therapy. Accordingly, we assessed the efficacy of these peptides in (i) two different lung disease models – acute lung inflammation and asthma in mice and (ii) using two differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Peptide-based gene delivery systems have many advantages over other non-viral ones, including biocompatibility, biodegradability, limited toxicity and large-scale production capabilities [ 21 , 22 ]. Arginine-rich peptides belonging to cationic cell penetrating peptides (CPPs) are effective for in vitro and in vivo gene delivery [ 23 , 24 , 25 ]. Previous studies have shown that CPPs crosslinked by disulfide bonds promote efficient gene transfection and low cytotoxicity, due to the fact that disulfide bonds can be split by intracellular reducing compounds as glutathione for to release DNA [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Peptide-based gene delivery systems have many advantages over other non-viral ones, including biocompatibility, biodegradability, limited toxicity and large-scale production capabilities [ 21 , 22 ]. Arginine-rich peptides belonging to cationic cell penetrating peptides (CPPs) are effective for in vitro and in vivo gene delivery [ 23 , 24 , 25 ]. Previous studies have shown that CPPs crosslinked by disulfide bonds promote efficient gene transfection and low cytotoxicity, due to the fact that disulfide bonds can be split by intracellular reducing compounds as glutathione for to release DNA [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, it was also possible to target a specific organ, as reported first for the NF55:pDNA nanoparticles [43]. Based on this result, Kurrikoff and colleagues performed in-depth analysis using PF14-and NF55-PBNs for the specific lung delivery of siRNA and pDNA using mice with acute lung inflammation and asthma [89]. Important anti-inflammatory effects were recorded in both disease models using siRNA targeting cytokine TNFα, resulting in decreased disease symptoms.…”
Section: Cell/organ Targetingmentioning
confidence: 89%
“…Based on this sequence, a novel amphipathic α-helical peptide, NF55, was designed for efficient in vivo DNA delivery by modifying the net charge and the helicity of the CPP [44,45]. More recently, Freimann and co-workers presented a new formulation approach called cryo-concentration for obtaining stable and homogeneous nanoparticles showing significantly higher bioactivity in vivo [89].…”
Section: Pepfect/nickfect Familymentioning
confidence: 99%
“…PF14 and NF55 preferentially transfect lung tissue upon their systemic administration with the complexed siRNA and pDNA encoding shRNA against cytokine TNFα in models of acute lung inflammation and asthma in mice, and showed efficient anti-inflammatory effects in both disease models [ 203 ].…”
Section: Targetingmentioning
confidence: 99%